Frequency-angular spectra of the stimulated Raman scattering parametric components under self-action - Ivanisik, А.І.; Isaenko, O.Iu.; Korotkov, P.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
It’s theoretically proved that in self-focusing mode of exciting radiation, selfphase modulation, and the relaxation oscillations of the nonlinear polarization amplitude, the frequency-angular structure of the parametric components of the stimulated Raman scattering has special features. Maximum of radiation energy shifts relative to Raman frequencies, and this shift depends on the scattering angle. The largest Stokes shift (about -10 cm⁻¹ ) of the maximum energy in the spectrum of parametric components corresponds to axial radiation and is determined by the size of the focal area, time of polarization existence as well as mismatch of the polarization wave vectors and parametric component. The obtained estimations of the self-phase modulation influence on radiation in the case of relaxation oscillations show that this influence is insignificant. The effect has been interpreted in terms of short-term phase matching.